2014
DOI: 10.1002/2013jb010409
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of strong ground motion due to thrust fault earthquakes

Abstract: (2014), Experimental investigation of strong ground motion due to thrust fault earthquakes, J. Geophys. Res. Solid Earth, 119, 1316-1336, doi:10.1002 Abstract Thrust fault earthquakes are studied in a laboratory earthquake setup previously used to investigate analog strike-slip seismic events. Dynamic mode II ruptures are generated along preexisting faults in an analog material, Homalite H-100, and their interaction with the free surface is studied for both sub-Rayleigh and supershear rupture speeds. High-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…Several numerical studies confirmed their results (Oglesby et al, 1998(Oglesby et al, , 2000aMa and Beroza, 2008;Nielsen, 1998;Gabuchian et al, 2017). Gabuchian et al (2014Gabuchian et al ( , 2017 most recently revisited this issue by means of experiments using homalite as a rock analogue. Beside the free-surface effects they focused on rupture velocity as a controlling factor for ground motion.…”
Section: Ground Motionmentioning
confidence: 80%
“…Several numerical studies confirmed their results (Oglesby et al, 1998(Oglesby et al, , 2000aMa and Beroza, 2008;Nielsen, 1998;Gabuchian et al, 2017). Gabuchian et al (2014Gabuchian et al ( , 2017 most recently revisited this issue by means of experiments using homalite as a rock analogue. Beside the free-surface effects they focused on rupture velocity as a controlling factor for ground motion.…”
Section: Ground Motionmentioning
confidence: 80%
“…The logic of studying the distribution of ETLs on the hanging-wall of faults is based on findings that, during earthquakes, ground motions are stronger on the hanging-wall than on the footwall of a dipping earthquake fault (Abrahamson and Somerville 1996;Yu and Gao 2001;Ulusay et al 2004). The proposed explanation for those observations is asymmetry of distribution of seismic energy as a function of fault geometry (Oglesby and Day 2002;Beavan et al 2012;Shi and Day 2013;Gabuchian et al 2014), although that is usually not the case because attenuation of ground motion is also a function of style-of-faulting (Campbell 1981;Abrahamson and Silva 1997;Bommer et al 2003). Nevertheless, studies have shown that ground motions on the hanging wall were stronger than on the footwall of the Yingxiu-Beichuan fault Lu et al 2010).…”
Section: Representation Of Fault Control On Susceptibility To Landslimentioning
confidence: 99%
“…However, the findings must be crossexamined further in relation to fault geometry because (a) the mainly thrust-slip southern part of the YingxiuBeichuan fault has a different geometry than its mainly strike-slip northern part (Fig. 3) and (b) attenuation of ground motion is also a function of fault geometry (Oglesby and Day 2002;Beavan et al 2012;Shi and Day 2013;Gabuchian et al 2014). In addition, the findings must be cross-examined further in relation to other factors that influence variations in ground motion (see Campbell (1981Campbell ( , 1997).…”
Section: Representation Of Fault Control On Susceptibility To Landslimentioning
confidence: 99%
See 1 more Smart Citation
“…Observations and understanding of supershear ruptures have important implications for seismic hazard and earthquake dynamics [Dunham et al, 2003;Xia et al, 2004;Dunham, 2007;Das, 2010;Mello et al, 2010;Schmedes et al, 2010]. For example, Gabuchian et al [2014] show that upward supershear rupture on a thrust fault would enhance the ground shaking by a factor of 2 to 3. Although the physics and conditions of the transition from subshear (V r < V S ) to supershear rupture are not yet fully understood, previous observations and theoretical studies indicate that high prestress and high seismic efficiency (e.g., a simple fault geometry) help promote supershear rupture [Zhang and Chen, 2006;Bouchon et al, 2010;Kaneko and Lapusta, 2010].…”
Section: Introductionmentioning
confidence: 99%